Households’ perceptions of service quality and economic valuation of electronic waste recycling in Putrajaya, Malaysia - Haron, Nazatul Faizah (2015)
The importance of electronic waste (e-waste) management became a growing concern,especially in developing countries and over international boundaries. Therefore, effective management systems need to be created and infrastructure facilities for recycling needs to be developed to prevent an accumulation of e-waste that contain hazardous materials in landfill areas. However, an understanding of people‟s willingness to recycle e-waste is important. This research aims to identify the perceptions of service quality, determinant factors of e-waste recycling, and examine the economic valuation on recycling preferences. Several methods were used in this research, namely, Critical Incident Technique (CIT),Factor Analysis (FA) and Choice Modelling (CM). A total of 600 respondents were randomly selected in nine precincts in Putrajaya. The CIT methods were used to analyse the satisfaction or dissatisfaction level. Five successful constructs were identified and prioritised, namely „Good Feeling‟, „Secured Environment‟, „Facilities and Efficiency‟, „Educational‟ and „Peer Pressure‟. Recovery strategies were also recorded and evaluated for response and recovery service dissatisfaction. Meanwhile,the FA method was used to identify the influencing factors in e-waste recycling with an applied logit model for regression. The most significant factors that contribute to recycling behaviour are: „Attitude‟, „Belief‟, „Convenience‟ and „Social Pressure‟, in addition to socioeconomic factors, such as „Education‟ and „Income‟. People who have a higher income and higher education levels are more likely to recycle. To examine the economic valuation in recycling preferences, choice modelling (CM) was used to evaluate the recycling service attributes with applied conditional logit (CL) to estimate marginal value of the attributes. The results suggest that people are concerned about separation of waste in recycling services The findings outline policy recommendations to policy makers, the waste management industry and consumers: especially when faced with existing issues on activities and recycling services. As recycling and environmental issues are gaining national attention, government agencies are charged with promoting and increasing recycling behaviour with an emphasis on the motivation and importance of information as necessary components of any campaign. Even though many local communities made recycling more accessible through a „drop-off program‟, that program alone however is not sufficient to optimise rates of recycling. Residents must understand details of how to recycle their e-waste with the help of accessible recycling information, providing rationale and motivation to individuals in order to promote recycling activity and guiding them in necessary recycling skills. In addition, greater exposure to environmental issues and recycling through public service announcements, public forum and media will help to enhance individual motivation as well as improving the recycling facilities to cope with problems in the provision of better services in the future.